2018
DOI: 10.3389/fendo.2018.00201
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Progesterone Elevation on the Day of Human Chronic Gonadotropin Trigger and Pregnancy Outcomes After Fresh Embryo Transfer in In Vitro Fertilization/Intracytoplasmic Sperm Injection Cycles

Abstract: Progesterone elevation (PE) during the late follicular phase of controlled ovarian stimulation in fresh embryo transfer in vitro fertilization (IVF)/intracytoplasmic sperm injection cycles has been claimed to be associated with decreased pregnancy rates. However, the evidence is not unequivocal, and clinicians still have questions about the clinical validity of measuring P levels during the follicular phase of stimulated cycles. We reviewed the existing literature aimed at answering four relevant clinical ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…Embryo transfer was conducted on day 3 after oocyte retrieval. All the patients received embryo transfer on day 3, except in the following cases: (a) serum estrogen >7,000 pg/mL on the trigger day, (b) more than 15 oocytes were retrieved, (d) the presence of uterine or endometrial abnormalities such as endometriosis, uterine myoma, endometrial polyps, or intrauterine adhesion, (e) an initial increase of progesterone over 1.5 ng/mL before the trigger day (18), or (f) the patient refused fresh embryo transfer. A maximum of two embryos were transferred.…”
Section: Methodsmentioning
confidence: 99%
“…Embryo transfer was conducted on day 3 after oocyte retrieval. All the patients received embryo transfer on day 3, except in the following cases: (a) serum estrogen >7,000 pg/mL on the trigger day, (b) more than 15 oocytes were retrieved, (d) the presence of uterine or endometrial abnormalities such as endometriosis, uterine myoma, endometrial polyps, or intrauterine adhesion, (e) an initial increase of progesterone over 1.5 ng/mL before the trigger day (18), or (f) the patient refused fresh embryo transfer. A maximum of two embryos were transferred.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have examining the subtle elevation in serum progesterone during the follicular phase of OS and its effect on cycle outcome have yielded conflicting results regarding pregnancy rate (summarized in [2][3][4][5]). Orvieto Kolibianakis et al [3] have demonstrated in their metaanalysis that progesterone elevation on the day of hCG administration was associated with a significantly decreased probability of clinical pregnancy in patients undergoing OS for IVF using GnRH antagonists (-ant).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent evidence suggests that progesterone elevation affects not only implantation but also embryo quality [4]. On the other hand, Esteves et al [5] have recently reviewed the existing evidence regarding late follicular phase progesterone rise and showed that progesterone elevation was mainly caused by the supraphysiological stimulation during OS and is not influenced by the type of gonadotropin used. Moreover, its detrimental effect on IVF outcome does not affect all patient populations equally and might be overcome by the availability of good-quality embryo.…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta-analysis comprising 63 eligible studies (55,199 fresh IVF cycles using either agonist or antagonist protocols) found that a high progesterone level (defined as progesterone levels ≥ 0.8 ng/mL) on the day of triggering is associated with a decreased probability of pregnancy [22]. In contrast, a recent review of the available evidence suggested that debate remains regarding the impact of late follicular phase progesterone elevation on fresh ET IVF/ICSI outcomes [23]. To further validate this prediction model, we performed a sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%